2020
DOI: 10.1002/aoc.5654
|View full text |Cite
|
Sign up to set email alerts
|

Two d10 metal–organic frameworks based on a novel semi‐rigid aromatic biscarboxylate ligand: Syntheses, structures and luminescent properties

Abstract: Two new d 10 metal-organic frameworks based on a novel semi-rigid aromatic biscarboxylate ligand, namely, [Zn (RGAA)(BPY) 1/2 ] (1) and [Cd 5 (μ 3-OH) 2 (RGAA) 4 ] (2) [H 2 RGAA = 4-(carboxymethyl)-2-ethoxybenzoic acid, BPY = 4,4 0-bipyridine], have been synthesized by the hydrothermal reaction, and characterized by Fourier transform-infrared, elemental analyses, X-ray single-crystal diffraction, powder X-ray diffraction and thermogravimetric analyses. Complex 1 displays a three-dimensional (3D) network with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 143 publications
0
2
0
Order By: Relevance
“…Among them, the sulfonate group has recently received much attention for its useful features, such as flexible coordination modes, binding preferences to metal ions, and widely bridging extension [ 15 , 16 ]. For instance, Wu and co-workers [ 17 ] used phenyl sulfonic acid, p -aminobenzene sulfonic acid, and p -methylbenzene sulfonic acid to synthesize three Co(II) coordination complexes under hydrothermal conditions. They found that the formation of hydrogen bonds and π–π stacking interactions can organize the architecture into a 3D supramolecular topology by connecting discrete molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the sulfonate group has recently received much attention for its useful features, such as flexible coordination modes, binding preferences to metal ions, and widely bridging extension [ 15 , 16 ]. For instance, Wu and co-workers [ 17 ] used phenyl sulfonic acid, p -aminobenzene sulfonic acid, and p -methylbenzene sulfonic acid to synthesize three Co(II) coordination complexes under hydrothermal conditions. They found that the formation of hydrogen bonds and π–π stacking interactions can organize the architecture into a 3D supramolecular topology by connecting discrete molecules.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the rational selection of organic ligands or coligands according to their lengths, rigidities, coordination modes and functional groups may provide the controllable CPs [14][15][16][17]. In various types of organic ligands, rigid ligands generally have conjugated systems and its structure is fixed; flexible ligands have complex structures and can rotate; semi-rigid ligands have the advantages of both rigid and flexible ligands, so they are favored by researchers in the synthesis of CPs [18,19]. Nitrogen-containing ligands are a great variety and can be as an excellent hydrogen bond receptor [20,21].…”
Section: Introductionmentioning
confidence: 99%